STUDENTS’ PERCEPTION IN APPLYING COOPERATIVE LEARNING IN EFL CLASSROOM - Liza Andhani Hidayati; Irma Kharisma; Intan Satriani (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
This study focuses on college students’ perceptions of cooperative learning in EFL classrooms. The purpose of the study is to know students’ opinion about applying cooperative learning in the classroom especially in EFL classroom. Case study was chosen as an approach in this study. Participants of this study were the final year students of Indonesian education study program. The numbers of participants were 33 students. The data were collected using questionnaire consisted of 20 (twenty) questions that relate with cooperative learning. The result of this research showed that the final year students of Indonesian education study program of IKIP Siliwangi Bandung had positive responses toward the implementation of Cooperative Learning. Besides that, it was found that students familiar with group activities in EFL classroom. To sum up, Cooperative Learning is a good approach for the students to learn English easily. Keywords: cooperative learning, EFL classroom, perception.